In-depth Learning Policy Analysis in the Indonesian Education System with the SMART Approach - Eka Aprilianty (Jurnal Pedagogi dan Pembelajaran, 2025)
The Indonesian education system continues to face fundamental challenges, including low literacy outcomes, the dominance of rote learning, and disparities in teacher competency and distribution. This study aims to analyze the learning policy in depth using the SMART approach. This study employed a qualitative descriptive design with an evaluative approach, using the SMART (Specific, Measurable, Achievable, Relevant, Time-bound) framework as its analytical lens. The research subjects consisted of official policy documents, curriculum guidelines, and academic literature on PM published between 2022 and 2025. Data were collected through document analysis, using a research instrument consisting of a document analysis sheet compiled based on the SMART framework. The results show that the PM policy is conceptually relevant to the demands of 21st-century education and is formulated with specific objectives. However, the policy lacks explicit quantitative indicators, measurable implementation targets, and a detailed operational roadmap. The study concludes that PM can serve as a strategic instrument for education reform only if accompanied by cross-sectoral collaboration, improved teacher policies, and measurable implementation strategies. The implication is that strengthening teacher capacity, recruitment systems, certification, and professional development must be parallel priorities to ensure PM's success in achieving quality education.